Effects of The Black cumin seeds (Niqella sativa Linn.) on Endometrial Mucins of Mature Rats; Histochemical Study - Hassan, Ahmed J.; Al-Baffar, Raith A.B.; Al-Baghdadi, Haythem A.; Al-Azawi, Hani T. (Journal of the Faculty of Medicine Baghdad, 2005)
Summary:Background: Nitre I la sativa Linn is a well known herb that is used by different societies, as food additive and as a medicinal herb: it used as a galactagouge for lactating women, and has long been described as an abortifacient-emmenagouge.Aim of the work: is to investigate the effect of crude black seeds on the endometrium and the pattern of it’s mucins, during the different phases of the Estrus cycle, making use of some special stains for the histochemical demonstration of mucins.Materials